SpecR Motorsport / Ahmad Junaidi Mohd Mokhtar ... [et al.] - Mohd Mokhtar, Ahmad Junaiadi; Abdullah, Alif Faisal; Mohd Rani, Mohd Zamrey; Zakaria, Mohd Zairy; Abu Bakar, Muhammad Azran (Faculty of Civil Engineering, 2002)
The red R emblem means Racing in Japan. Thus, our company chose this red R logo as the trademark for our company and reminds of our customer about our workshop. The red color also shows the strength of our company in doing task and fulfills anything that comes in our way.